Artificial Intelligence (AI) sebagai Katalisator Pedagogis: Transformasi Digital dalam Merancang Soal High Order Thinking Skill - Nurhajarurahmah, St Zulaiha; Tasni, Nurfaida; Azis, Suhartini; Syukriani, Andi; Agustini, Sri (Universitas Pahlawan Tuanku Tambusai, 2025)
The training on creating Higher Order Thinking Skills (HOTS) questions using artificial intelligence (AI) platforms such as Quizizz aims to enhance the skills of prospective educators in designing assessment questions that encourage critical and creative thinking. The urgency of this training is crucial in the context of current digital education, where technology and higher-order thinking skills (HOTS) are essential to face the challenges of the 21st century. The benefits of this training include improving participants' abilities to design HOTS questions based on Bloom's taxonomy and utilizing technology to create more interactive and applicable questions. Data analysis was conducted both quantitatively and qualitatively. Quantitatively, the analysis was done by comparing pre-test and post-test scores to measure the participants' improvement in understanding HOTS and using Quizizz. Additionally, data from practical observations and evaluation questionnaires were used to assess participants' participation, enthusiasm, and independence in designing questions. The analysis results showed that 80% of participants were able to design HOTS questions at cognitive levels C4 and C5, and 75% of participants successfully utilized Quizizz's features.